2012
DOI: 10.3892/mmr.2012.892
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein 7 suppresses the progression of hepatic fibrosis and regulates the expression of gremlin and transforming growth factor β1

Abstract: Abstract. Bone morphogenetic protein 7 (BMP-7), a member of the transforming growth factor (TGF)-β superfamily, counteracts the effect of TGF-β through different signaling pathways, and gremlin is considered as one of the antagonists of BMP-7. The aim of this study was to investigate the antifibrotic effect of BMP-7, and to clarify the expression patterns of gremlin and TGF-β1 in the progression of hepatic fibrosis after treatment with BMP-7. A mouse liver fibrosis model was induced by hypodermic injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…These results connect correlate? with previous studies on liver and renal fibrosis ( Zeisberg et al, 2003 ; Kinoshita et al, 2007 ; Yang et al, 2012 ), suggesting that BMP-7 is one of the possible mechanisms in reversing liver fibrosis by counteracting TGF-β and EMT ( Zeisberg et al, 2003 ).…”
Section: Discussionsupporting
confidence: 83%
“…These results connect correlate? with previous studies on liver and renal fibrosis ( Zeisberg et al, 2003 ; Kinoshita et al, 2007 ; Yang et al, 2012 ), suggesting that BMP-7 is one of the possible mechanisms in reversing liver fibrosis by counteracting TGF-β and EMT ( Zeisberg et al, 2003 ).…”
Section: Discussionsupporting
confidence: 83%
“…There is data showing that on a model of hepatic fibrosis, the BMP-7 RNA levels in the liver are the same whether the animals are treated or not with BMP-7. Also, treatment with BMP-7 increases the levels of Gremlin, which is an antagonist that prevents BMP-7's ligation to its receptor [27]. Despite the different variables that can influence the effect of in vivo treatment with BMP-7, our work is the first description of the anti-fibrotic role of BMP-7 in an allergic setting, such as asthma.…”
Section: Discussionmentioning
confidence: 91%
“…Balanced TGF-β and BMP signaling has been proposed to be crucial for the progression of fibrosis [ 42 ]. Meng et al suggested that TGF-β1 is activated upon fibrosis, disrupting the balance between TGF-β1 and BMP7 resulted in the suppression of BMP7 expression and its target genes [ 33 , 43 ]. Similarly, in the present study, a mutually inhibitory relationship between TGF-β1 and BMP3 was observed in both human patients and a murine fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining The lung biopsies of 83 patients were performed immunohistochemical staining to determine the expression of BMP3 and TGF-β. Among these patients, the biopsies of 47 cases were used to establish the tissue arrays following a method previously described (Shanghai Outdo Biotech Co. Ltd) [ 33 ], which were possess the integrated five-years following-up data. Briefly, tissue arrays were constructed from 154 tissue samples collected from 47 lung thoracoscopic surgery specimens of patients with IPF and INSIP (Each specimen was randomly taken 3 samples to construct tissue arrays), and 13 normal tissue specimens (Each specimen was randomly taken 1 sample for construction).…”
Section: Methodsmentioning
confidence: 99%